Prevalence of Adynamic Bone Disease among Hemodialysis Patients - Mazharulhaq, Taleah Tahir, Aimal Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Aim of current study is to determine the association of adynamic bone disease among patients of hemodialysis. Study Design: Cross sectional Place and Duration: Institute of Kidney Diseases Hayatabad Peshawar during the period from January 2021 to June 2021. Methods: There were 82 patients of both genders had chronic kidney disease were presented. Patients on maintenance HD had their treatments administered by a Fresenius machine 4008S connected to a polysulfone membrane dialyzer and a dialysate solution comprising 32 mmol/L of bicarbonate and 1.75 mmol/L of calcium. All of the patients in the study had been on dialysis for over a year, and none of them had any signs of acute sickness or active liver disease. SPSS 22.0 was used to analyze all data. Results: Mean age of the patients was 43.4±8.26 years and had mean BMI 22.4±6.30 kg/m2. There were 48 (58.5%) males and 34 (41.5%) females. Mean duration of hemodialysis was 4.6±5.19 years. Frequency of DM was found in 24 (29.3%) cases. Frequency of vitamin D therapy was found in 55 (67.1%) cases. We found that 29 (35.4%) patients had adynamic bone disease and 21 (25.6%) cases had hyperparathyroidism. Significantly higher number of patients had bone pain among all cases. Conclusion: We concluded in this study that the prevalence of adynamic bone disease was 35.4%. Among patients of ABD most were ages between 25-45 years and were males with severe bone pain. Keywords: Hemodialysis, Diabetes Mellitus, Adynamic Bone Disease, Hyperparathyroidism